Unexpected high frequency of unspecific reactivities by testing pre‐epidemic blood specimens from Europe and Africa with SARS‐CoV‐2 IgG–IgM antibody rapid tests points to IgM as the Achilles heel. Issue 4 (22nd November 2020) - Mboumba Bouassa, Ralph‐Sydney; Péré, Hélène; Tonen‐Wolyec, Serge; Longo, Jean De Dieu; Moussa, Sandrine; Mbopi‐Keou, Francois‐Xavier; Mossoro‐Kpinde, Christian Diamant; Grésenguet, Gérard; Veyer, David; Bélec, Laurent
Abstract: We aimed to evaluate the rates of false‐positive test results of three rapid diagnostic tests (RDTs) for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐specific immunoglobulin G (IgG) and IgM detection. Two serum panels from patients hospitalized in Paris, France, and from patients living in Bangui, Central African Republic, acquired before the 2019 COVID‐19 outbreak, were tested by 3 CE IVD‐labeled RDTs for SARS‐CoV‐2 serology (BIOSYNEX® COVID‐19 BSS [IgG/IgM]; SIENNA™ COVID‐19 IgG/IgM Rapid Test Cassette; NG‐Test® IgG–IgM COVID‐19). Detectable IgG or IgM reactivities could be observed in 31 (3.43%) of the 902 IgG and IgM bands of the 3 RDTs used with all pre‐epidemic sera. The frequencies of IgG/IgM reactivities were similar for European (3.20%) and African (3.55%) sera. IgM reactivities were observed in 9 European and 14 African sera, while IgG reactivity was observed in only 1 African serum (15.1% vs. 0.66%). The test NG‐Test® IgG–IgM COVID‐19 showed the highest rates of IgG or IgM reactivities (6.12% [18/294]), while the test BIOSYNEX® COVID‐19 BSS (IgG/IgM) showed the lowest rate (1.36% [4/294]). Some combinations of 2 RDTs in series allowed decreasing significantly the risk of false‐positive test results. Our observations point to the risk of false‐positive reactivities when using currently available RDT for SARS‐CoV‐2 serological screening, especially for the IgM band, even if the test is CE IVD‐labeled and approved by national health authorities, and provide the rational basis for confirmatory testing by another RDT in case of positive initial screening.